2006
DOI: 10.1128/aem.03072-05
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Large Signature-Tagged Mini-Tn 5 Transposon Library and Its Application to Mutagenesis of Sinorhizobium meliloti

Abstract: Sinorhizobium meliloti genome sequence determination has provided the basis for different approaches of functional genomics for this symbiotic nitrogen-fixing alpha-proteobacterium. One of these approaches is gene disruption with subsequent analysis of mutant phenotypes. This method is efficient for single genes; however, it is laborious and time-consuming if it is used on a large scale. Here, we used a signature-tagged transposon mutagenesis method that allowed analysis of the survival and competitiveness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 39 publications
1
79
0
Order By: Relevance
“…The iolR, iolD, and iolE mutants of S. meliloti 2011 contain mTn5-STM::gusA insertions, obtained by transposon mini-Tn5 signature-tagged mutagenesis (mTn5-STM), in the same orientation as the respective genes, creating transcriptional fusions that allow the investigation of iolRDE gene expression by determining the ␤-glucuronidase activity (27). (The mTn5-STM mutation in the iolC mutant is oriented in the opposite direction as the iolC gene, and no transposon-induced iolB mutant is available in S. meliloti strain 2011.…”
Section: Resultsmentioning
confidence: 99%
“…The iolR, iolD, and iolE mutants of S. meliloti 2011 contain mTn5-STM::gusA insertions, obtained by transposon mini-Tn5 signature-tagged mutagenesis (mTn5-STM), in the same orientation as the respective genes, creating transcriptional fusions that allow the investigation of iolRDE gene expression by determining the ␤-glucuronidase activity (27). (The mTn5-STM mutation in the iolC mutant is oriented in the opposite direction as the iolC gene, and no transposon-induced iolB mutant is available in S. meliloti strain 2011.…”
Section: Resultsmentioning
confidence: 99%
“…One of the differences in symbiosis between M. loti and S. meliloti is that the latter bacteroid undergoes terminal differentiation through endoreduplication, causing it to lose reproductive capacity, whereas the former maintains reproductive capacity during symbiosis (28). Therefore, it is significant that large-scale mutant libraries of mapped transposon insertion mutants have been constructed to enable STM screening of both M. loti and S. meliloti (34,41). Complementary functional genomics in these two species should provide a complete picture of the symbiosis between rhizobia and legumes.…”
Section: Discussionmentioning
confidence: 99%
“…STM has since been applied to a number of pathogenic or symbiotic bacteria (for a review, see reference 27). An STM library was constructed for the symbiotic bacterium S. meliloti by using 412 transposons with unique tags that can be detected by hybridization to microarrays (34). A pilot screening of this library showed that a number of genes relevant to symbiosis or competition could be identified (35).…”
mentioning
confidence: 99%
“…We used the S. meliloti strain Rm2011 (referred to here as strain 2011; [48,49] and its RNase E and RNase J mutants 2011rne :: Tn5 and 2011rnj :: Tn5, which harbour mini-Tn5 insertions in the respective genes rne (SMc01336) and rnj (SMc01929) [7,31,37]. The mutant strains are referred to here as 2011rne and 2011rnj, respectively.…”
Section: Strains Plasmids Cultivation and Cloningmentioning
confidence: 99%
“…The role of S. meliloti RNase J in rRNA maturation was studied using a mutant with a mini-Tn5 insertion destroying the only one rnj gene [31,37]. The rRNA maturation defect of this RNase J mutant was complemented perfectly by constitutive ectopic rnj expression [31].…”
Section: Introductionmentioning
confidence: 99%